Elite and sub elite flat water sprint kayakers performance comparison: A preliminary result - Lok, Y. L.; Smith, R.; Sinclair, P. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of the present study was to compare the effects of using a fixed and swivel seat between elite and sub elite kayakers: conducted on a 200 metre simulation race in the laboratory setting. One elite and one sub elite male sprint kayaker participated in this study, performing on both seat conditions. Significantly increased results were found in paddle force and stroke rate using the swivel seat for the sub elite kayaker (p<0.05). Correlation values of more than 0.6; p<0.05 were obtained in the foot force and paddle force of the sub elite kayaker. Further research with more participants is required to obtain important information of an efficient paddling execution by the kayakers at different skill levels.